Hubungan Kadar Asam Urat Dengan Kadar HbA1c Pada Penderita DM Tipe 2 Peserta Prolanis (Program Pengelolaan Penyakit Kronis) - Munawaroh, Sri; Panjaitan, Dedi Ansyari (Universitas Muhammadiyah Sumatera Utara, 2025)
Abstract: Diabetes mellitus (DM) is a metabolic disease characterized by hyperglycemia due to abnormalities in insulin secretion, insulin action or both. DM cases in the world reach 463 million people, and it is estimated that it will increase in 2045 to reach 700 million people. Almost all provinces in Indonesia have seen an increase including North Sumatra, which increased from 1.8% to 2% in 2018. HbA1c has become the most widely used and accepted test to monitor glycemic control in individuals with diabetes. This study aims to determine the relationship between uric acid levels and HbA1c levels in prolanis patients with type 2 DM. Descriptive analytical research with a cross sectional research design of data collection using secondary data from medical records. The study sample was patients diagnosed with type 2 DM disease who entered the inclusion criteria and exclusion was obtained using purposive sampling with a total of 37 patients. Data analysis was carried out using a person correlation test with a meaning limit if p0.05. The results showed that there was a significant relationship between uric acid levels and HbA1c levels (p = 0.014 and r = 0.402). This means that the higher the HbA1c level, the higher the uric acid level. There is a significant relationship between uric acid levels and HbA1c levels.